2018
DOI: 10.1038/s41467-018-05705-4
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of climate warming on boreal tree growth may be transitory

Abstract: Predicted increases in temperature and aridity across the boreal forest region have the potential to alter timber supply and carbon sequestration. Given the widely-observed variation in species sensitivity to climate, there is an urgent need to develop species-specific predictive models that can account for local conditions. Here, we matched the growth of 270,000 trees across a 761,100 km2 region with detailed site-level data to quantify the growth responses of the seven most common boreal tree species in East… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
173
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(197 citation statements)
references
References 61 publications
(65 reference statements)
19
173
5
Order By: Relevance
“…The predicted increase in timber growth with temperature is congruent with other studies reporting enhanced productivity in a warmer world (Boisvenue & Running, ; D'Orangeville et al, ). However, recent research has shown that reduced winter snowpack and increased soil freezing are negatively affecting the growth rate of sugar maple ( Acer saccharum ), one of the study region's most important tree species (Reinmann, Susser, Demaria, & Templer, ).…”
Section: Discussionsupporting
confidence: 88%
“…The predicted increase in timber growth with temperature is congruent with other studies reporting enhanced productivity in a warmer world (Boisvenue & Running, ; D'Orangeville et al, ). However, recent research has shown that reduced winter snowpack and increased soil freezing are negatively affecting the growth rate of sugar maple ( Acer saccharum ), one of the study region's most important tree species (Reinmann, Susser, Demaria, & Templer, ).…”
Section: Discussionsupporting
confidence: 88%
“…That is, continuous warming and drying conditions may exacerbate moisture stress, and therefore, productivity reduction in these ecosystems. Interestingly, a recent tree‐ring based study revealed that while 2°C of warming may increase overall forest productivity, additional warming could reverse this trend and lead to substantial moisture stress (D'Orangeville et al, ). Also, multiple warming experiments confirm the dynamism of climate constraints on plant growth in the southern boreal forest and highlight the vulnerability of the ecosystem to excess warming and drying (e.g., Reich et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Divergent latitudinal responses with climate warming have also been reported for growth of Picea mariana, suggesting that it could better withstand warming at northernmost locations than at southern locations (D'Orangeville et al, ). These enhanced growth effects at the northern range limit, however, could be transitory for this species as warming continues (D'Orangeville et al, ), especially for juvenile stages which are more sensitive to climate stress than adult stages (Kueppers et al, ; Munier et al, ).…”
Section: Discussionmentioning
confidence: 99%